Tribological characterisation of polymer composites for hydropower bearings: Experimentally developed versus commercial materials. (October 2021) - Somberg, Julian; Saravanan, Prabakaran; Vadivel, Hari Shankar; Berglund, Kim; Shi, Yijun; Ukonsaari, Jan; Emami, Nazanin
Abstract: To mitigate the effects of downstream lubricant spillage from hydroelectric power plants, environmentally friendly lubricants are required. For the sustainable operation of oil-free bearings, the development of high performance bearing materials is crucial. In this study, the tribological performance of PPS and UHMWPE-based composites, incorporating various reinforcements, such as graphene oxide, is evaluated and compared with five commercial materials. Experiments were performed under different lubricating conditions; Dry, water, and using a glycerol-based environmentally adaptive lubricant (EAL). The use of water inhibited an adequate transfer film, which increased wear for most materials. EAL lubrication showed a significant reduction in friction (up to 98%) when compared to dry conditions. The experimentally developed PPS composite provided superior tribological properties, especially under water-lubricated conditions. Graphical Abstract: ga1 Highlights: Two graphene oxide-based self-lubricating polymer composites were developed. The tribological performance of the developed composites and five commercial materials in different lubrication conditions was evaluated. The developed composites provided a superior friction and wear performance, especially under water lubricated conditions. The used environmentally adaptive lubricant was effective in significantly reducing both friction and wear for all materials.